Measuring self-esteem instability through a single-administration scale: Still a fruitless endeavor?. (January 2017) - Howard, Matt C.
Abstract: Studies on self-esteem instability (SEI) must obtain multiple measurements of self-esteem, such as daily for two weeks, to calculate SEI. This measurement method is called the "gold standard." The intensive nature of the gold standard forces SEI be studied through multiple-day, controlled, student-sample designs, which restricts generalizability and possible variables studied. We attempt to address these concerns through creating a new single-administration SEI scale, called the SEI Measure (Studies 1 and 2), and analyzing the relationship of the SEI Measure and prior single-administration SEI scales with the gold standard (Studies 3 and 4). The SEI Measure and existing scales only have moderate correlations with the gold standard, suggesting that they do not adequately gauge SEI. As these studies are the most robust investigation into single-administration SEI scales to date, we suggest that the study of such scales should be refocused, and our results also provide direction for new research avenues. Innovative single-administration SEI measures, such as implicit measures, may still adequately gauge SEI, and authors should consider perceived SEI separately from SEI itself. Perceived SEI may be an important aspect of self-perceptions that leads to distinct personal outcomes that are not predicted by SEI or other commonly studied variables. Highlights: Self-esteem instability (SEI) is gauged through many measurements of self-esteem. We study the relationship four SEI scales with the traditional measurement method. The scales only have moderate correlations with the traditional measurement method. A valid single-administration SEI scale may be impossible to create.